2014
DOI: 10.1111/jsm.12487
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Review: Breast Development in Trans Women Receiving Cross-Sex Hormones

Abstract: Introduction In trans women (male-to-female transsexual persons), cross-sex hormone therapy is administered to induce feminization. Breast development is an important part of feminization for most trans women. Aim The aim of this study is to assess the effect of cross-sex hormone therapy on breast development in adult trans women. Additionally, we aimed to investigate the benefit or harm of administration of progestogens on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 62 publications
1
61
0
1
Order By: Relevance
“…The regimen used does not appear to influence the final breast outcome. 10 There are however differences in anatomy between the male and female thorax; therefore, despite maximal response to oestrogen therapy, more than half the patients require breast augmentation so that the breast contour appears proportionate for their larger body frame. 9 With oestrogen treatment the skin texture becomes finer, and there is a reduction in the growth of facial hair.…”
Section: Physical Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regimen used does not appear to influence the final breast outcome. 10 There are however differences in anatomy between the male and female thorax; therefore, despite maximal response to oestrogen therapy, more than half the patients require breast augmentation so that the breast contour appears proportionate for their larger body frame. 9 With oestrogen treatment the skin texture becomes finer, and there is a reduction in the growth of facial hair.…”
Section: Physical Effectsmentioning
confidence: 99%
“…A recent meta-analysis looking at breast development in transwomen found no evidence that there is any additional benefit of progesterone on breast growth over oestrogen alone. 10 Moreover, progestin in combination with oestrogen may increase the incidence of cardiovascular events and has a trend towards increasing levels of breast cancer when we look at the large-scale trials of hormone replacement in natal females. 22,23 These risks were not seen in the oestrogen-only arm of these trials, suggesting that progesterone is detrimental for both cardiovascular and breast health.…”
Section: Adjunctive Therapiesmentioning
confidence: 99%
“…But despite its importance, only a few low-quality studies have been done to investigate the effect of cross-sex hormone therapy on this outcome. 39 Breast development starts within 2–3 months after initiation of combined oestrogen and anti-androgen treatment, and takes up to 2 years to complete. In a longitudinal study by Meyer and colleagues, 34 breast hemi-circumference increased by 14 cm after 3 years of oestrogen therapy.…”
Section: Expected Time Course and Physical Changesmentioning
confidence: 99%
“…40 No evidence exists that the addition of progesterone improves breast development. 39 Cross-sex hormone treatment has also been reported to lead to softening of the skin and feminine hair growth, but systematic studies have not been done. 35,41 …”
Section: Expected Time Course and Physical Changesmentioning
confidence: 99%
“…A meta-analysis found no additional benefit for breast development when comparing progesterone plus oestrogen to oestrogen alone. 17 We advise patients that oestrogen-only hormone therapy is the best and safest option, as progesterone is not produced during the breast development phase of physiological female puberty, and trans women do not have endometria to protect. At a cellular level, progesterone reverses oestrogeninduced cell proliferation and, more importantly, evidence in cis women has shown that adding progesterone to oestrogen therapy is associated with increased risk of cardiovascular disease and breast cancer.…”
Section: Other Medicationsmentioning
confidence: 99%